The effect of light waves on polarization mode disperts - Erlinda, Sopya; Veriyanti, Velia; Saktioto, Saktioto; Abdullah, Hewa Yaseen (Science, Technology and Communication Journal, 2022)
Optical fiber is a medium that spreads information in the form of light waves. The quality of the optical fiber can be determined by knowing the dispersion value of the polarization mode which is one of the characteristics of the optical fiber by using a single-mode optical fiber design simulation method using the OptiFiber software. The single-mode optical fibers used in the simulation are SMF-28, SMF-28e, SMF-28e+, SMF-28e+ LL, SMF-28 ULL. A good quality SMF for long-distance communication is an SMF that has a small PMD value.